A comparative investigation of the synergistic correlation (mechanical-hydrophobicity/hydrophilicity vs. structural behaviors) of a series of surface-metalized polyacrylonitrile fibers by silver nanoparticles (AgPAN): An in-situ surface metallization protocol. (10th November 2022) - Kara, Gheffar Kh.; esmaeili, Elaheh; Kehtari, Mousa; Ghafourian, Rayhaneh; Tadjarodi, Azadeh
Research problem: The demand for polymeric materials is increasing day by day, provided that they have excellent virtues to meet desired needs. The best way to obtain high-quality polymeric materials was surface treatment in multiple methods. All the methods that have been used were expensive, multi-stage, harmful to the environment, and other shortages. Therefore, we sought in our paper to invent and develop a surface metallization protocol under green and safe conditions, based on integrating two safe methods for preparing nanomaterials (electrospinning/ultrasound) in one-pot. Aim of this work: The main objective of this work is to answer a question that has been neglected in other papers: how does in-situ metallization affect the crystalline behavior of the semi-crystalline phase of the PAN matrix depending on different amounts of MA NPs and their synergy for the rest of the properties (morphological and structural) is presented, in first degree. In the second degree, an explanation of the synergy mechanism between the mechanical/hydrophilic properties and the modified structural properties of metalized fibers has explained. Results: Here, an unaccustomed and green methodology to metalize the polyacrylonitrile, PAN, surface is reported with the intention of fashioning of a stable fibrous structure and the best specifications. The in-situ metallization process is essentially based on a loading of various amount of silver nanoparticles, as MA NPs "MA NPs", (1 wt%, 4 wt%, 7 wt% and 10 wt%), which prepared by ultrasound irradiation assisted with a little amount of a reducer system (hydrazine/NaOH), on the PAN surface. The physiochemical characterization of as-synthesized fibrous samples was consisted of two parts: (i) characterization of sample nature (utilizing of XRD and UV-Vis. techniques), (ii) the chemical structure/morphological characterization (utilizing FESEM, TEM and AFM techniques) with performing all relevant measurements. From crystalline and UV-Vis. assessments, the observed shift in the diffraction peaks towards lower angles and slight shifts in the absorption bands of PAN(1 0 0) in the 1AgPAN and 4AgPAN samples, containing smaller-sized nanoparticles, are overt results of an improvement in the crystalline traits of the parent matrix. The FT-IR data revealed the intensification and overlapping of the IR-bands "C= N, C≡ N, N-H, C=O and O-H" without band shifting for fibrous samples with low content of MA NPs (1AgPAN and 4AgPAN samples). The intercalation of the MA NPs between the chains of the molecular matrix and the strong interconnection/hydrogen bonds between both components explain not only the change of the crystalline properties of the crystalline matrix but also the homogeneous distribution and creation of a stable layer of the MA NPs on the 0AgPAN surface, confirmed by the FESEM and TEM images. The results of the study of mechanical properties showed that the loading of small spherical particles onto the polymeric matric, in particular 1AgPAN and 4AgPAN samples, was positively reflected on the improvement of the mechanical performances and the related values, not in the 7AgPAN and 10AgPAN samples. Because the MA NPs have a hydrophobic character, loading them onto the bare polymeric fiber surface made the metalized fibers a stronger hydrophobic than that of hydrophilic character, which is consistent with differences in surface roughness (increasing Ra values). The main focus of this paper was to study the synergy of structural properties with each other. So, the results of the synergistic relationship study showed that the low amount of the MA NPs led to a comprehensive and positive correlation between all structural properties and in turn affected the mechanical properties-hydrophobic/hydrophilic properties. Noting that the fibers of the 1AgPAN and 4AgPAN samples had the best structural stability, compared to the fibers of the 0AgPAN, 7AgPAN and 10AgPAN samples, when they were: decreasing in Z value, increasing fiber diameter/particle size "P.S.", increasing RCR and C.D. values and decreasing D.D, alteration in values obtained of the mechanical behavior and the increasing of contact angle "CA" values for water "H2 O" droplets and decreasing for ethylene glycol "EG". As a final result, the changes observed in the aforementioned measurements were reasonably regular and gradual for fibers with low MA NPs content, while the same measurements were significantly deteriorated in the case of fibers with higher MA NPs contents.